KEWENANGAN PROSES PENYELIDIKAN DAN PENYIDIKAN PIHAK KEPOLISIAN TERHADAP NOTARIS SETELAH TERBITNYA UNDANG - UNDANG JABATAN NOTARIS NOMOR 2 TAHUN 2014 - SARIYONO SARIYONO (PREMISE LAW JURNAL, 2017)
The problem of the research was how about a deed drawn up by a Notary according to UUJN, it is duty of the Police to find out the truth about it. Therefore, the title of the research was “the Authority of the Process of Inquiry and Investigation by the Police on a Notary after the issuance of UUJN No. 2/2014, The conclusion of the research was that the authority of the Police in the process of inquiry and investigation on a Notary after the issuance of UUJN No. 2/2014 was that both parties should understand their own authority respectively according to Law. When a Notary has the problem with the deed, the Police can summon him as a witness/defendant. On the other hand, a Notary has the right of objection in the secrecy of his deed according to Article 4 in conjunction with Article 16 in conjunction with Article 54 of UUJN No. 2/2014. Meanwhile, based on Article 170, paragraph 1 of KUHAP and Article 1909, paragraph 2, fiqure 3e of KUHPerdata, the Police should understand the principle of presumed legality (Vermoedanvan Rechtmatigheid) or Presumption lustae Causa; in this case, a notarial deed should be considered legal until there is someone who claims that it is illegal, Here, the Police should state that it is legal until someone claims that it is legally defective, and the result of the research can be used for the next researches by the Police and a Notary; an MOU can be made between the Police management and the Indonesian Notarial Association.Keywords: Inquiry and Investigation, Police Force, Notary, UUJN No. 2/2014